Academic achievement critical factors and the bias and variance decomposition - Costa-Mendes, Ricardo (2022)
Costa-Mendes, R., Cruz-Jesus, F., Oliveira, T., & Castelli, M. (2022). Academic achievement critical factors and the bias and variance decomposition: evidence from high school students’ grades. In Papers of 6th Canadian International Conference on Advances in Education, Teaching & Technology 2022: Papers proceedings (pp. 54-62). (International Multidisciplinary Research Journal; Vol. Special Issue, No. Conferences - Proceedings). Unique Conferences Canada. https://imrjournal.info/2022/EduTeach2022Proceedings1.pdf